2016
DOI: 10.1021/jacs.6b01376
|View full text |Cite
|
Sign up to set email alerts
|

Scalable, Metal- and Additive-Free, Photoinduced Borylation of Haloarenes and Quaternary Arylammonium Salts

Abstract: We report herein a simple, metal- and additive-free, photoinduced borylation of haloarenes, including electron-rich fluoroarenes, as well as arylammonium salts directly to boronic acids. This borylation method has a broad scope and functional group tolerance. We show that it can be further extended to boronic esters, and carried out on gram scale as well as under flow conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
140
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(143 citation statements)
references
References 116 publications
1
140
0
1
Order By: Relevance
“…We recently reported that haloarenes, including electron-rich fluoroarenes, as well as quaternary arylammonium salts readily react with diboron compounds to produce aromatic boronic acids and esters (Fig. 1a-c) under photochemical activation conditions 29 . A similar photoinduced borylation method was also developed by Li 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that haloarenes, including electron-rich fluoroarenes, as well as quaternary arylammonium salts readily react with diboron compounds to produce aromatic boronic acids and esters (Fig. 1a-c) under photochemical activation conditions 29 . A similar photoinduced borylation method was also developed by Li 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Homolytic and heterolytic cleavage of the Ar–X bond followed by the homolytic substitution at boron 21 in B 2 (OR) 4 were proposed as key steps in this process.…”
mentioning
confidence: 99%
“…The experimental and computational data available for the photoinduced Ar–X monoborylation, 19,22 point to a solvent-cage-assisted radical pathway (Scheme 2) for the dual 1,2-C–H/C–X borylation reaction in isopropanol. Photoinduced homolysis is very efficient for bromo- and iodoarenes in low- and medium polarity solvents.…”
mentioning
confidence: 99%
See 2 more Smart Citations